La medición de la resiliencia (2007)
ABSTRACT: To identify techniques and instruments to measure resilience. Material and Methods: An internet bibliographic review was carried under a resiliency measurement describer. Studies dealing with the establishment of resiliency measurement methods were selected. Results: The review shows that techniques and measurement instruments for the measurement of resilience can be divided in three groups: protective tests, psychometric tests and imagenology tests. This division matches the principal theoretical approaches to the concept of resilience. Psychometric tests are the more developed and some of them could be successfully used in other studies of the theme. However protective and imagenology test show interesting approaching potential to the concept especially in clinical and qualitative work. Discussion: The various factors intervening in resilience and the different theoretical approaches to the concept hinder the construction and measurement process. Dealing with this task researchers have to take sides regarding the different deﬁnitions of resilience leading them to leave aside some important aspects of the concept. Conclusion: It is highly convenient to carry out research with mixing methodological designs to be able to have a deeper insight to understand the phenomenon or resilience that would enable us to reach a wider comprehensive and integrative consensus regarding the concept and then to advance further in the design of for the integral measurement of the various aspects of resilience.